Severe impact of introduced scale insects on Island Trees threatens endemic finches at the Tristan da Cunha archipelago. (November 2020) - Dilley, Ben J.; Davies, Delia; Glass, Trevor; Bond, Alexander L.; Ryan, Peter G.
Abstract: Inaccessible and Nightingale Islands are uninhabited islands in the Tristan da Cunha archipelago, central South Atlantic Ocean. Over the past decade, the spread and impacts of two species of invasive scale insects have increased steadily, severely affecting the Island Tree Phylica arborea woodlands and the endemic large-billed finches Nesospiza spp., which feed extensively on Phylica fruit. The first species, Greedy Scale Hemiberlesia rapax, causes local canopy diebacks and slightly reduced fruit loads. On Inaccessible, it appears to be only locally distributed, but on Nightingale it has spread rapidly since 2012 and now infects 95% of the Island Trees. The second species, Brown Soft Scale Coccus hesperidum and its associated sooty mould Seiridium phylicae, has expanded its range at Inaccessible since 2011, and colonised Nightingale by 2016. At Inaccessible, repeat transects between 2011 and 2018 show that Phylica fruit loads are markedly reduced and many large trees have died. Numbers of male Dunn's Finches N. acunhae dunnei, which rely on Phylica fruits, have declined by 50% in the last decade in heavily infested woodlands at Inaccessible Island, and some males in the most badly affected woodland are paired with small-billed Finches N. a. acunhae . If the trees on Nightingale follow a similar fate, the persistence of the endemic Wilkins' Finch N. wilkinsi will be under severe threat. The potential use of a biological agent to control C. hesperidium infestations should be investigated, since without swift and effective mitigation, we predict the health of these woodlands will degrade rapidly. Highlights: Invasive sap-sucking scale insects severely affect trees on an oceanic island. Trees produce less fruit and many large trees have collapsed since 2011. The persistence of the fruit-reliant endemic island finches is under severe threat. Biological control may be an option to curb scale insect infestations.